PENGARUH PROMOSI DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN SMARTPHONE SAMSUNG DI PT ACCENTUATES SAMSUNG CENTER MEDAN - Tarigan, Lala Latifah (Yayasan Cita Cendekiawan Al Khwarizmi, 2023)
This study aimsto determine theeffect of promotionand product qualityon purchasing decisionsfor Samsung smartphones, this type of research uses quantitative research methods with sources primary and secondary data. The number of samples of this research is 125 respondents determined using Slovi formula and accidental sampling technique namely handling the sample based on necessity, that is anyone who happens to meet the research can be used as a sample. This study uses SPSS 25 as a data processing tool. The results ofthis study shows that there is a significant influence between promotions on purchasing decisions on Samsung smartphones and there is no significant influence between product quality on purchasing decisions on Samsung smartphones while simultaneously a significant influence between promotions and product quality is on purchasing decisions on Samsung smartphones